Usage Intention of Food Delivery Apps During Covid-19 - Ayman, Nurhuda; Nazihah, Nurin Fatin; Izzati, Nurin; Syamimi, Nurin (International Journal of Tourism and Hospitality in Asia Pasific, 2022)
This study aims to look into the role of food delivery services in increasing user satisfaction and thereby improving business success. During the COVID-19 pandemic, entrepreneurs, such as small entrepreneurs, had enormous obstacles in running their businesses. Consumers are begging for takeout meals to be delivered as social separation becomes the new norm. Large and small enterprises are looking forward to collaborating with these third-party delivery providers. Providing deliveries can help eateries cut costs during this time of disruption while also making the transition back to normal working circumstances easier after COVID-19 is no longer a problem. This research was carried out using an online questionnaire provided on the Google Forms platform, which collected information from 100 food delivery consumers in Malaysia and also India. This research reveals that Covid-19 will increase demand for user satisfaction indicators such as perceived service quality, price affordability, ease of access, service awareness, and customer loyalty. Having achieved this, customers will be motivated and continue to use online platforms, leading to increase sales for business owners in the Covid-19 situation. Keywords: Covid-19, Customer loyalty, Delivery food, Ease of access, Perceived service quality, Price affordability, Service awareness.